Adiponectin Inhibits PDGF-induced Mesangial Cell Proliferation: Regulation of Mammalian Target of Rapamycin-mediated Survival Pathway by Adenosine 5-Monophosphate-activated Protein Kinase - Su, Y.-X.; Deng, H.-C.; Zhang, M.-X.; Long, J.; Peng, Z.-G. (Hormone and Metabolic Research, 2012)
An aberrant proliferation of mesangial cells (MCs) is one of the more important features of diabetic nephropathy (DN). Adiponectin, an adipocyte-derived hormone, has been associated with type 2 diabetes, a known cause of DN. Recent studies have suggested that adiponectin has a protective effect on the kidney. To elucidate the potential protective mechanism of adiponectin on kidney, we investigated the effects of adiponectin on platelet-derived growth factor (PDGF)-induced cell proliferation and intracellular signaling pathways in cultured Human MCs (HMCs). PDGF-induced HMC proliferation was significantly inhibited by the co-treatment of adiponectin. Adiponectin alone had no effect on HMC proliferation. The mammalian target of rapamycin (mTOR) and 40 S ribosomal S6 kinase 1 (S6K1) were activated by PDGF stimulation in HMCs. PDGF-induced mTOR and S6K1 phosphorylations were significantly attenuated by the co-treatment of adiponectin in HMC. Adiponectin alone had no effects on PDGF-receptor autophosphorylation by PDGF. We also confirmed that the inhibitory effect of adiponectin on PDGF-induced HMC proliferation was significantly suppressed by compound C, an adenosine 5′-monophosphate-activated protein kinase (AMPK) inhibitor. From these findings, it is implied that adiponectin could attenuate renal dysfunction associated with MC disorders through AMPK-mTOR signal pathway.
Keywords: adiponectin; cytokines; diabetic nephropathy